<h3>
Answer: D. y = -x</h3>
======================================================
Explanation:
Point T is at (-2,1)
When we reflect it over the line x = 0, aka the y axis, we use the rule
so T(-2,1) becomes T ' (2, 1). The x coordinate flipped in sign, while the y coordinate stays the same.
Then the final transformation is reflecting over y = -x using the rule
. Therefore, the point (2,1) moves to (-1, -2) which is where T'' is located in the diagram.
You apply the same two transformations for the points R and S to get R'' and S'' respectively.
Note: A composition of two reflections, where the lines of reflection aren't parallel, form a rotation. In this case, we have a 90 degree counterclockwise rotation when going from triangle RST to triangle R''S''T''.